1969
DOI: 10.1111/j.1432-1033.1969.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Primary Structure of Human Fibrinogen. Isolation and Characterization of N-Terminal Fragments from Plasmic Digests

Abstract: Two N-terminal fragments of a(A)-chain and /l(B)-chain in human fibrinogen have been isolated from a plasmic hydrolyzate. The fragment from the u(A)-chain consisted of 43 amino acid residues including two half-cystine residues. On treatment with thrombin, this fragment produced two other peptides in addition to fibrinopeptideA and its analogues. One was a tripeptide, Gly-Pro-Arg, and the other a peptide containing 24 amino acid residues having N-terminal valine. The partial amino acid sequence of the a(A)-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(71 citation statements)
references
References 57 publications
0
71
0
Order By: Relevance
“…Fibrinopeptides A and B are cleaved off the a(A) and P(B) chains respectively by thrombin. The resulting product is fibrin [3,4]. Sulfitolysis of fibrinogen results in the cleavage of the disulfide bridges [5] , and the resulting S-sulfo chain derivatives have been separated by paper [ 51, starch gel electrophoresis [6] and column chromatography [S, 71. More recently, the S-sulfo chain derivatives from bovine [8] and human [9] fibrinogen have been isolated on carboxymethyl cellulose using a stepwise [8] and gradient [9] sodium acetate buffer system.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinopeptides A and B are cleaved off the a(A) and P(B) chains respectively by thrombin. The resulting product is fibrin [3,4]. Sulfitolysis of fibrinogen results in the cleavage of the disulfide bridges [5] , and the resulting S-sulfo chain derivatives have been separated by paper [ 51, starch gel electrophoresis [6] and column chromatography [S, 71. More recently, the S-sulfo chain derivatives from bovine [8] and human [9] fibrinogen have been isolated on carboxymethyl cellulose using a stepwise [8] and gradient [9] sodium acetate buffer system.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanogen bromide cleavage of the protein S15 was performed in 70% formic acid at room temperature for 20 h and the resulting peptides were separated by gel filtration on Biogel P-30 in a 5% acetic acid solution. Amino acid compositions of the peptides were determined with an automatic amino acid analyzer (JEOL; type JLC6AH) after hydrolysis with 5.7 N HCl containing 0.02% mercaptoethanol at 108°C for 20 h. The amino acid sequence of the peptides was determined by manual Edman degradation as modified by Iwanaga et al [7] and the PTH-amino acids were identified by thin-layer chromatography on silica gel plates.…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid analyses of cardiotoxin and the peptides generated by cyanogen bromide cleavage or tryptic digestion of the RCM-toxin were performed with the standard method using an Hitachi KLA 3B amino acid analyzer. Sequence analyses were conducted by the modified Edman procedure [19,20], and the phenylthiohydantoin amino acids were identified by thin layer chromatography employing several solvent systems [21][22][23]. Carboxypeptidase A digestion was performed according to standard methods [24].…”
Section: Methodsmentioning
confidence: 99%